1984
DOI: 10.1007/bf02619632
|View full text |Cite
|
Sign up to set email alerts
|

Primary and long term epithelial cell cultures from human fetal normal colonic mucosa

Abstract: Primary and passaged cultures of normal colon epithelial cells, derived from human fetuses (13 to 17 wk of conceptual age) have been established. These cultures have been passaged 16 times thus far. The cultures have been initiated and maintained in medium consisting of 50% Dulbecco's minimum essential medium and 50% Ham's F12 medium and supplemented with antibiotics (penicillin, 100 U/ml; streptomycin, 100 micrograms/ml); ascorbic acid, 40 micrograms/ml; L-isoleucine, 50 micrograms/ml; epidermal growth factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 8 publications
1
42
0
Order By: Relevance
“…Several earlier studies demonstrated long-term propagation of primary epithelial cell cultures from rodent and human colon [1,3,4,6,7]. Some showed long-term replication potential and functional differentiation, suggesting that the cultures may have contained stem cell populations, although such characterization was not performed.…”
Section: Organ Culturementioning
confidence: 99%
See 3 more Smart Citations
“…Several earlier studies demonstrated long-term propagation of primary epithelial cell cultures from rodent and human colon [1,3,4,6,7]. Some showed long-term replication potential and functional differentiation, suggesting that the cultures may have contained stem cell populations, although such characterization was not performed.…”
Section: Organ Culturementioning
confidence: 99%
“…The most widely used basal media for intestinal epithelium include MEM [1,2,3,9], DMEM [7,8], and Ham's F-12 [50]. Siddiqui and Chopra [4] used 1:1 combination of DMEM and Ham's F-12 for culturing human fetal colon epithelial cells. Selection of one basal medium over another may be made to achieve stable osmolarity and reduce culture shock.…”
Section: Primary and Long-term Intestinal Epithelial Cell Culturementioning
confidence: 99%
See 2 more Smart Citations
“…The colonic mucosa has proved difficult to study because this tissue is often heavily contaminated by bacteria and fungi and because the proliferative cells constitute a single layer lying deep in the crypts of Leiberkuhn. Despite attempts to develop longterm cultures of colonic epithelial cells from different species (3)(4)(5), proliferation of these cells has not been demonstrated for more than a few days (6,7). There have been attempts to immortalize or transform intestinal epithelial cells by using known immortalizing viral proteins (8).…”
Section: Introductionmentioning
confidence: 99%